Toward a better understanding of the influence of repetitive negative thinking in alcohol use disorder: An examination of moderation effect of metacognitive beliefs and gender. (December 2020) - Hamonniere, Tristan; Laqueille, Xavier; Vorspan, Florence; Dereux, Alexandra; Illel, Katia; Varescon, Isabelle
Highlights: The 'capture mental resources' factor is an independent predictor of alcohol use disorder (AUD) severity. Repetitive thinking is a significant predictor of AUD severity only for people with high negative metacognition. Repetitive thinking predicted AUD severity only for men with high beliefs about the need to control their thoughts. Repetitive thinking predicted AUD severity for men with high positive beliefs about emotional self-regulation. Repetitive thinking and metacognitive beliefs could be promising therapeutic targets. Abstract: Repetitive negative thinking (RNT), the most studied forms of which are depressive ruminations and anxious worry, is a unique transdiagnostic process responsible for the development and maintenance of many mental disorders. Over the past decade, studies have shown that RNT could be involved in the development and maintenance of alcohol use disorder (AUD). However, to date, little is known about the factors that can influence this relationship, even though some theoretical and empirical arguments suggest that variables such as gender or metacognitive beliefs may determine the role of RNT in the onset of symptoms. The aim of the present study was to test the moderation effect of metacognitive beliefs and gender in the relationship between RNT and AUD. Eighty-one AUD patients were administered measures of AUD severity, RNT, metacognitive beliefs about thinking and alcohol use, anxiety, and depression. Results indicated that the 'capture mental resources' factor of RNT is a significant predictor of AUD severity, independent from anxiety and depression, and that this effect is moderated by metacognitive beliefs and gender. RNT is a significant predictor of AUD severity only for people with high negative beliefs about thoughts regarding uncontrollability and danger. Furthermore, RNT was found to predict AUD severity only for men with high beliefs about the need to control thoughts and for men with high positive beliefs about emotional self-regulation. Treatments that reduce attentional impairments caused by RNT and modify dysfunctional metacognitive beliefs could be promising for some patients with AUD.